Análisis Multitemporal Del Crecimiento De La Zona Urbana En El Municipio De Mosquera, Cundinamarca (2025)
This work deals with the issue of change from rural to urban areas in the municipality of Mosquera Cundinamarca, using multitemporal analysis using satellite images over a period of 21 years. The main characteristic to define each of the rural and urban areas was the CORINE LAND COVER methodology used by IDEAM.